"Ni-kshay SETU", A Digital Health Intervention for Capacity Building in Tuberculosis under the National TB Elimination Program in India: A Comprehensive mHealthapp review - Bhavesh Modi; Bhavna Puwar (Indian Association of Preventive and Social Medicine, 2023)
This mHealthapplication review explores the evolution, design, and impact of Ni-kshay SETU, a digital health intervention tailored for India's National Tuberculosis Elimination Program (NTEP). Faced with escalating TB incidences, the NTEP prioritized capacity-building, leading to the conception of Ni-kshay SETU. This review describes the narrative of Ni-kshay SETU's concept from the beginning to the present day. It starts with the National Strategic Plan 2017-25, which says that capacity building of health care workers is important for reduction of tuberculosis morbidity and mortality by 2025.The digital platform materialized as a web app with Android and iOS versions, constituting a user-friendly interface. The app, embodying a ready reckoner and decision-making tool, offers cadre-speciic modules in local languages, promoting ease of comprehension and applicability. The app's development, rooted in a consultative process, aligns with the nuanced needs of healthcare personnel across various geographies and cadres. With more than 40,400 subscribers and 1,450,000 visits, Ni-kshay SETU serves as a notable example of digital health intervention, providing a comprehensive and context-aware approach to TB care. However, it's important to acknowledge the limitations of Ni-kshay SETU. While the app aims to address various challenges in TB care, its effectiveness is contingent on factors such as digital literacy and access to smartphones. Additionally, the app's success relies on consistent updates and continuous user engagement for its usage, posing potential challenges in sustaining the momentum.In summary, Ni-kshay SETU is not just a tool for building capacity but also acts as a driver for affordable digital solutions in areas with limited resources, aiming to strengthen healthcare systems on the path to eliminating TB.